2016
DOI: 10.1097/md.0000000000005195
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of trastuzumab-induced cardiotoxicity in breast cancer

Abstract: Background:Trastuzumab targets the human epidermal growth factor receptor 2 oncogene and in combination with first-line therapy results in significantly improved survival outcomes and has thus become standard of care in both adjuvant and metastatic settings. While it is estimated that 1% to 4% of patients treated with trastuzumab will develop heart failure and ∼10% will experience a reduction in left ventricular ejection fraction (LVEF), the patient risk factors associated with trastuzumab-induced cardiotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 42 publications
1
40
0
2
Order By: Relevance
“…Cardiotoxicity is a serious side effect which is already found in both cytostatic and molecularly targeted therapies. [ 35 , 36 ] Meanwhile, RIHD also has long been recognized. It usually includes pericardial disease, myocardial fibrosis, ischemic heart disease, valvular disease, arrhythmias, autonomic changes, and cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiotoxicity is a serious side effect which is already found in both cytostatic and molecularly targeted therapies. [ 35 , 36 ] Meanwhile, RIHD also has long been recognized. It usually includes pericardial disease, myocardial fibrosis, ischemic heart disease, valvular disease, arrhythmias, autonomic changes, and cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…As hyperlipidemia has been implicated in promoting cardiac inflammation, cancer patients, like all patients, should receive standard risk assessment based on the 2019 American College of Cardiology/American Heart Association (ACC/AHA) primary prevention guidelines to see if they would benefit from lipid lowering therapy [27,30]. Diabetes is another major risk factor which has been shown to increase the risk of cancer treatment-related cardiotoxicity in several studies, and it is critical to optimize management at the initiation of cancer therapy [27,31,32]. A few studies have suggested that genetic components may impact a patient's susceptibility to developing cancer therapy-related cardiac dysfunction.…”
Section: Who Is At Risk?mentioning
confidence: 99%
“…A recent meta-analysis of almost 30,000 women treated with trastuzumab reported an incidence for severe cardiotoxicity of 3% (95%CI 2.41-3.64) at three year follow-up [51]. Older age, a history of anthracycline administration, hypertension, obesity and diabetes are risk factors for trastuzumab-induced LV dysfunction [64,65].…”
Section: Non-anthracycline-induced Cardiotoxicitymentioning
confidence: 99%